Exterior material for power storage device and power storage device using same
Patent Information
- Application Number
- JP2020119066
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-10
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-07-10
AI Technical Summary
【0017】 本発明によれば、室温環境下及び高温環境下の両方で優れたラミネート強度を確保できると共に、深絞り成型性にも優れた蓄電装置用外装材及びこれを用いた蓄電装置を提供することができる。
Smart Images

Figure 0007631687000002 
Figure 0007631687000003 
Figure 0007631687000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an exterior material for an electricity storage device and an electricity storage device using the same. [Background technology]
[0002] Known examples of power storage devices include secondary batteries such as lithium ion batteries, nickel metal hydride batteries, and lead storage batteries, as well as electrochemical capacitors such as electric double layer capacitors. Due to the miniaturization of portable devices or the limitations of installation space, there is a demand for further miniaturization of power storage devices, and lithium ion batteries with high energy density have attracted attention. Metal cans have traditionally been used as exterior materials for lithium ion batteries, but multilayer films that are lightweight, have high heat dissipation properties, and can be produced at low cost have come to be used.
[0003] A lithium ion battery using the above multilayer film as an exterior material is called a laminated lithium ion battery. The exterior material covers the battery contents (positive electrode, separator, negative electrode, electrolyte, etc.) and prevents moisture from penetrating into the battery. A laminated lithium ion battery is manufactured, for example, by forming a recess in a part of the exterior material by deep drawing, accommodating the battery contents in the recess, folding back the remaining part of the exterior material, and heat sealing the edges (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-101765 A Summary of the Invention [Problem to be solved by the invention]
[0005] Meanwhile, research and development is being conducted on a power storage device called an all-solid-state battery as a next-generation battery of lithium-ion batteries. An all-solid-state battery is characterized by using a solid electrolyte as the electrolyte, rather than an organic electrolyte. While a lithium-ion battery cannot be used at temperatures higher than the boiling point of the electrolyte (about 80°C), an all-solid-state battery can be used at temperatures exceeding 100°C, and the conductivity of lithium ions can be increased by operating it under high temperature conditions (for example, 100 to 170°C).
[0006] However, when a laminated all-solid-state battery is manufactured using the above-mentioned multilayer film as an exterior material, if the heat resistance of the exterior material is insufficient, the interlayer adhesion cannot be ensured in a high-temperature environment, and the laminate strength may decrease, resulting in a decrease in the sealing property of the package of the all-solid-state battery. As shown in Patent Document 1, the exterior material has a structure in which, for example, a base material layer, a metal foil layer (barrier layer), and a sealant layer are laminated via an adhesive layer or the like, but the adhesion between the base material layer and the metal foil layer is likely to decrease in a high-temperature environment. In addition, epoxy-based adhesives are known as heat-resistant adhesives, but the cured product of the epoxy-based adhesive is likely to be highly brittle, and the deep drawability and laminate strength required for the exterior material and room temperature environment are likely to be insufficient.
[0007] The present invention has been made in consideration of the above problems, and aims to provide an exterior material for an electricity storage device that can ensure excellent laminate strength both in room temperature and high temperature environments and also has excellent deep draw formability, and an electricity storage device using the same. [Means for solving the problem]
[0008] In order to achieve the above object, the present disclosure provides an exterior material for an electricity storage device including at least a base layer, a barrier layer, and a sealant layer in this order, The present invention provides an exterior packaging material for an electricity storage device, characterized in that an adhesive layer containing a polyurethane compound and a polyamideimide resin is provided between the base layer and the barrier layer.
[0009] The adhesive layer containing the polyurethane-based compound has higher toughness than the cured film of the epoxy-based adhesive, and can obtain excellent deep drawing formability and excellent laminate strength at room temperature environment. However, for example, the laminate strength in a high temperature environment of 170 °C or higher is not sufficient. The polyurethane-based compound composed of the reaction product of polyester polyol and the nurate of isophorone diisocyanate (IPDI-n) is relatively excellent in heat resistance, but even in this case, the laminate strength in a high temperature environment of 170 °C or higher is not sufficient.
[0010] Although the polyamideimide resin is relatively brittle and thus inferior in toughness, it is excellent in heat resistance. By blending this with the above polyurethane-based compound to form an adhesive layer, sufficient laminate strength can be exhibited even in a high temperature environment of 170 °C or higher, and the deep drawing formability is also excellent. Moreover, even after deep drawing molding in this way, high laminate strength in a high temperature environment can be maintained.
[0011] In the adhesive layer, when the solid content of the polyamideimide resin is A mass% with respect to the solid content of the polyurethane-based compound, it is desirable to satisfy 1.0 mass% < A. On the contrary, when the solid content A of the polyamideimide resin with respect to the solid content of the polyurethane-based compound is 1.0 mass% or less, the laminate strength in a high temperature environment may be insufficient. Also, it is desirable to satisfy A < 20.0 mass%. On the contrary, when the solid content A of the polyamideimide resin with respect to the solid content of the polyurethane-based compound is 20.0 mass% or more, the deep drawing formability is inferior.
[0012] Next, it is desirable that the number average molecular weight Mn of the polyamideimide resin satisfies 3000 < Mn < 36000. On the contrary, when the number average molecular weight Mn of the polyamideimide resin is 3000 or less, the glass transition temperature and softening temperature of this polyamideimide resin will be low, and there is a risk that the laminate strength in a high-temperature environment will be insufficient. Further, when the number average molecular weight Mn of the polyamideimide resin is 36000 or more, it is difficult to dissolve in a solvent, and thus it becomes difficult to apply and form an adhesive layer.
[0013] Next, the polyurethane-based compound may be composed of a reaction product of at least one polyol resin and at least one polyfunctional isocyanate compound. At this time, as the polyol resin, at least one polyol resin selected from the group consisting of polyester polyol, acrylic polyol, and polycarbonate polyol can be used. When the polyol resin is composed of these polyester polyols, acrylic polyols, or polycarbonate polyols, both the laminate strength and moldability in a high-temperature environment are improved.
[0014] Further, as the polyfunctional isocyanate compound, at least one isocyanate multimer selected from the group consisting of alicyclic isocyanate multimers and isocyanate multimers containing an aromatic ring in the molecular structure can be used. When the polyfunctional isocyanate compound is composed of these alicyclic isocyanate multimers or isocyanate multimers containing an aromatic ring in the molecular structure, both the laminate strength and moldability are improved. The reason is not clear, but it can be presumed that it is due to the fact that the alicyclic isocyanate multimer has a bulky molecular structure, so the molecular chain is difficult to unwind even in a high-temperature environment. Also, in the isocyanate multimer containing an aromatic ring in the molecular structure, due to the intermolecular interaction, the cohesive force increases, and the heat resistance of the cured film itself increases, so it can be presumed that the laminate strength increases.
[0015] Next, with respect to the number of hydroxyl groups contained in the polyol resin, the polyfunctional isocyanate The ratio (NCO / OH) of the number of isocyanates contained in the compound is preferably 1.5 < NCO / OH < 40.0.
[0016] When the number of isocyanates contained in the curing agent (polyfunctional isocyanate compound) of the polyurethane-based compound is sufficiently larger than the number of hydroxyl groups contained in the main agent (polyol resin) (NCO / OH >> 1.0), the heat resistance is improved. When the NCO groups are sufficiently more than the OH groups in this way, the curing agents react with each other to form by-products such as urea resin and biuret resin. Since these urea resins and biuret resins contain active hydrogen groups, they interact with the polar groups in each interface, increasing the interfacial adhesion force. As a result, it can be presumed that the heat resistance is improved.
Advantages of the Invention
[0017] According to the present invention, it is possible to provide an exterior material for a power storage device that can ensure excellent laminate strength both at room temperature and high temperature environments, and is also excellent in deep drawing formability, and a power storage device using the same.
Brief Description of the Drawings
[0018] [Figure 1] It is a schematic cross-sectional view of an exterior material for a power storage device according to an embodiment of the present disclosure. [Diagram 2] It is a schematic cross-sectional view of an exterior material for a power storage device according to an embodiment of the present disclosure. [Diagram 3] It is a perspective view of a power storage device according to an embodiment of the present disclosure.
Modes for Carrying Out the Invention
[0019] Hereinafter, preferred embodiments of the present disclosure will be described in detail with appropriate reference to the drawings. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and redundant descriptions are omitted. Also, the dimensional ratios in the drawings are not limited to the illustrated ratios.
[0020] Fig. 1 is a cross-sectional view showing a schematic diagram of an embodiment of the exterior material for a power storage device according to the present disclosure. As shown in Fig. 1, the exterior material (exterior material for a power storage device) 10 of this embodiment is a laminate including a base layer 11, a first adhesive layer 12a provided on one side of the base layer 11, a barrier layer 13 having first and second corrosion prevention treatment layers 14a, 14b on both sides provided on the side of the first adhesive layer 12a opposite the base layer 11, a second adhesive layer 12b provided on the side of the barrier layer 13 opposite the first adhesive layer 12a, and a sealant layer 16 provided on the side of the second adhesive layer 12b opposite the barrier layer 13. Here, the first corrosion prevention treatment layer 14a is provided on the surface of the barrier layer 13 facing the base layer 11, and the second corrosion prevention treatment layer 14b is provided on the surface of the barrier layer 13 facing the sealant layer 16. In the exterior packaging material 10, the base material layer 11 is the outermost layer and the sealant layer 16 is the innermost layer. That is, the exterior packaging material 10 is used with the base material layer 11 facing the exterior side of the electricity storage device and the sealant layer 16 facing the interior side of the electricity storage device.
[0021] Each layer constituting the packaging material 10 will now be described in detail.
[0022] <Base material layer 11> The base layer 11 provides heat resistance in the sealing process when manufacturing the electricity storage device and plays a role in suppressing the occurrence of pinholes that may occur during molding and distribution. In particular, in the case of an exterior material for a large-scale electricity storage device, the base layer 11 can also provide scratch resistance, chemical resistance, insulation, and the like.
[0023] The base layer 11 is preferably a layer made of a resin film formed of an insulating resin. Examples of the resin film include stretched or unstretched films such as polyester film, polyamide film, and polypropylene film. The base layer 11 may be a single layer film made of any of these resin films, or a laminate film made of two or more of these resin films.
[0024] Among these, polyester film and polyamide film are preferable as the base layer 11 because of their excellent moldability, and polyester film is more preferable. These films are preferably biaxially stretched films. Examples of polyester resins constituting polyester films include polyethylene terephthalate (PET). Examples of polyamide resins constituting polyamide films include nylon 6, nylon 6,6, copolymers of nylon 6 and nylon 6,6, nylon 6,10, polymetaxylylene adipamide (MXD6), nylon 11, nylon 12, etc. Among polyamide films, nylon 6 (ONy) is preferable because of its excellent heat resistance, puncture strength, and impact strength.
[0025] Examples of the stretching method for the biaxially stretched film include a sequential biaxial stretching method, a tubular biaxial stretching method, a simultaneous biaxial stretching method, etc. From the viewpoint of obtaining better deep drawing formability, the biaxially stretched film is preferably one stretched by a tubular biaxial stretching method.
[0026] In addition, the base layer 11 preferably has a peak melting temperature higher than the peak melting temperature of the sealant layer 16. When the sealant layer 16 has a multi-layer structure, the peak melting temperature of the sealant layer 16 means the peak melting temperature of the layer with the highest peak melting temperature. The peak melting temperature of the base layer 11 is preferably 290°C or higher, more preferably 290 to 350°C. Examples of resin films that can be used as the base layer 11 and have a peak melting temperature in the above range include nylon film, PET film, polyamide film, and polyphenylene sulfide film (PPS film). As the base layer 11, a commercially available film may be used, or the base layer 11 may be formed by coating (application of a coating liquid and drying). The base layer 11 may have a single layer structure or a multi-layer structure, and may be formed by applying a thermosetting resin. In addition, the base layer 11 may contain, for example, various additives (for example, a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, a tackifier, etc.).
[0027] Melting peak temperature T of the base layer 11 11 and the melting peak temperature T of the sealant layer 16 16 The difference (T 11 -T 16 ) is preferably 20° C. or more. When this temperature difference is 20° C. or more, deterioration of the appearance of the packaging material 10 due to heat sealing can be more sufficiently suppressed.
[0028] The thickness of the substrate layer 11 is preferably 5 to 50 μm, more preferably 6 to 40 μm, further preferably 10 to 30 μm, and particularly preferably 12 to 30 μm. When the thickness of the substrate layer 11 is 5 μm or more, the pinhole resistance and insulating properties of the packaging material for an electricity storage device 10 tend to be improved. If the thickness of the substrate layer 11 exceeds 50 μm, the total thickness of the packaging material for an electricity storage device 10 becomes large, which is undesirable because it may be necessary to reduce the electric capacity of the battery.
[0029] <First adhesive layer 12a> The first adhesive layer 12a is a layer that bonds the base material layer 11 and the barrier layer 13. In the present invention, the first adhesive layer 12a must contain a polyurethane compound and a polyamideimide resin. An adhesive layer containing a polyurethane compound has high toughness, and can obtain excellent deep-drawing formability and excellent laminate strength in a room temperature environment. On the other hand, polyamideimide resin has excellent heat resistance, and by blending this with the polyurethane compound to form an adhesive layer, sufficient laminate strength between the base material layer 11 and the barrier layer 13 in a high-temperature environment of, for example, 170°C or higher and excellent deep-drawing formability of the packaging material 10 can be obtained, and the packaging material 10 after deep-drawing can maintain high laminate strength between the base material layer 11 and the barrier layer 13 in a high-temperature environment.
[0030] When the solid content of the polyamideimide resin is A mass% with respect to the solid content of the polyurethane-based compound, it is desirable to satisfy 1.0 mass% < A < 20.0 mass%, and particularly desirable to satisfy 10.0 mass% < A < 20.0 mass%. Further, the number average molecular weight Mn of the polyamideimide resin is desirably 3000 < Mn < 36000.
[0031] Next, the polyurethane-based compound may be composed of a reaction product of at least one or more polyol resins and at least one or more polyfunctional isocyanate compounds. The type of polyol resin may be arbitrary, but at least one polyol resin selected from the group consisting of polyester polyol, acrylic polyol, and polycarbonate polyol can be preferably used. In this case, both the laminate strength between the base material layer 11 and the barrier layer 13 in a high-temperature environment and the moldability of the exterior material 10 are improved.
[0032] Also, the type of the polyfunctional isocyanate compound may be arbitrary, but at least one isocyanate multimer selected from the group consisting of alicyclic isocyanate multimers and isocyanate multimers containing an aromatic ring in the molecular structure can be preferably used. In this case, both the laminate strength and the moldability are improved.
[0033] Examples of the alicyclic isocyanate multimer include, for example, the nurate form of isophorone diisocyanate (IPDI-nurate).
[0034] Examples of the isocyanate multimer containing an aromatic ring in the molecular structure include the adduct form of tolylene diisocyanate (TDI-adduct). Also, the adduct form, biuret form, and nurate form of diphenylmethane diisocyanate are examples of the isocyanate multimer containing an aromatic ring in the molecular structure. Further, examples of the isocyanate multimer containing an aromatic ring in the molecular structure include the adduct form, biuret form, and nurate form of xylylene diisocyanate.
[0035] Preferably, a polyester polyol is used as at least a part of the polyol resin, and an IPDI-nurate is used as at least a part of the polyfunctional isocyanate compound, and the polyurethane-based compound is produced by reacting the two. The exterior material 10 having the first adhesive layer 12a containing the polyurethane-based compound composed of the reaction product of the polyester polyol and the IPDI-nurate is particularly excellent in the laminate strength between the base material layer 11 and the barrier layer 13 in a high-temperature environment and the moldability of the exterior material 10.
[0036] In a specific adhesive layer, the content of the isocyanate groups derived from IPDI-nurate in the polyfunctional isocyanate compound is 5 to 100 mol% based on 100 mol% of the total amount of the isocyanate groups contained in the polyfunctional isocyanate compound, and may be 25 to 95 mol%, or may be 50 to 75 mol%. When this content is 5 mol% or more, the laminate strength in a high-temperature environment can be ensured, and the occurrence of delamination when exposed to a high temperature after deep drawing molding can be suppressed. On the other hand, the above content may be 100 mol%, but may be less than 100 mol% by using a polyfunctional isocyanate compound other than IPDI-nurate in combination. When the above content is 95 mol% or less, the laminate strength and deep drawing moldability at room temperature tend to be further improved by the combined effect of other polyfunctional isocyanate compounds.
[0037] In a specific adhesive layer, it is desirable that the ratio (NCO / OH) of the number of isocyanate groups contained in the polyfunctional isocyanate compound to the number of hydroxyl groups contained in the polyol resin is 1.5 < NCO / OH < 40.0. When the number of isocyanate groups contained in the curing agent (polyfunctional isocyanate compound) of the polyurethane-based compound is sufficiently larger than the number of hydroxyl groups contained in the main agent (polyol resin) (NCO / OH >> 1.0), the heat resistance is improved. When the polyurethane-based compound is composed of the reaction product of the polyester polyol and the IPDI-nurate, the optimum value of the above numerical value NCO / OH is 20. When the number of isocyanate groups contained in the curing agent (polyfunctional isocyanate compound) of the polyurethane-based compound is sufficiently larger than the number of hydroxyl groups contained in the main agent (polyol resin) (NCO / OH >> 1.0), the heat resistance is improved. When the polyurethane-based compound is composed of the reaction product of the polyester polyol and the IPDI-nurate, the optimum value of the above numerical value NCO / OH is 20.
[0038] <Barrier layer 13> The barrier layer 13 has a water vapor barrier property that prevents moisture from penetrating into the inside of the electricity storage device. The barrier layer 13 also has extensibility for deep drawing. As the barrier layer 13, for example, various metal foils such as aluminum, stainless steel, copper, etc., or metal vapor deposition films, inorganic oxide vapor deposition films, carbon-containing inorganic oxide vapor deposition films, films provided with these vapor deposition films, etc. can be used. As the film provided with the vapor deposition film, for example, an aluminum vapor deposition film or an inorganic oxide vapor deposition film can be used. These can be used alone or in combination of two or more. As the barrier layer 13, a metal foil is preferable, and an aluminum foil is more preferable, in terms of mass (specific gravity), moisture resistance, processability, and cost.
[0039] As the aluminum foil, a soft aluminum foil that has been annealed can be preferably used from the viewpoint of imparting desired ductility during molding, but it is more preferable to use an aluminum foil containing iron for the purpose of imparting further pinhole resistance and ductility during molding. The content of iron in the aluminum foil is preferably 0.1 to 9.0 mass%, more preferably 0.5 to 2.0 mass%, in 100 mass% of the aluminum foil. When the iron content is 0.1 mass% or more, an exterior material 10 having better pinhole resistance and ductility can be obtained. When the iron content is 9.0 mass% or less, an exterior material 10 having better flexibility can be obtained. As the aluminum foil, an untreated aluminum foil may be used, but it is preferable to use an aluminum foil that has been degreased in order to impart electrolyte resistance. When the aluminum foil is degreased, the degreased treatment may be performed on only one side of the aluminum foil, or on both sides.
[0040] The thickness of the barrier layer 13 is not particularly limited, but taking into consideration the barrier properties, pinhole resistance, and processability, it is preferably 9 to 200 μm, and more preferably 15 to 100 μm.
[0041] <First and second corrosion prevention treatment layers 14a, 14b> The first and second corrosion prevention layers 14a and 14b are layers provided on the surface of the barrier layer 13 to prevent corrosion of the metal foil (metal foil layer) constituting the barrier layer 13. The first corrosion prevention layer 14a plays a role in increasing the adhesion between the barrier layer 13 and the first adhesive layer 12a. The second corrosion prevention layer 14b plays a role in increasing the adhesion between the barrier layer 13 and the second adhesive layer 12b. The first corrosion prevention layer 14a and the second corrosion prevention layer 14b may be layers of the same configuration or layers of different configurations. The first and second corrosion prevention layers 14a and 14b (hereinafter also simply referred to as "corrosion prevention layers 14a and 14b") are formed, for example, by degreasing, hydrothermal conversion, anodizing, chemical conversion, or a combination of these treatments.
[0042] Examples of the degreasing treatment include acid degreasing and alkaline degreasing. Examples of the acid degreasing include a method using an inorganic acid such as sulfuric acid, nitric acid, hydrochloric acid, or hydrofluoric acid alone or a mixture of these. In addition, by using an acid degreasing agent in which a fluorine-containing compound such as monosodium ammonium difluoride is dissolved in the inorganic acid as described above, not only can the aluminum be degreased, but also a passive aluminum fluoride can be formed, which is effective in terms of corrosion resistance, particularly when an aluminum foil is used for the barrier layer 13. Examples of the alkaline degreasing include a method using sodium hydroxide or the like.
[0043] As an example of hydrothermal conversion treatment, aluminum is immersed in boiling water containing triethanolamine. One example is the boehmite treatment in which aluminum foil is immersed in the treatment.
[0044] An example of the anodizing treatment is an alumite treatment.
[0045] The chemical conversion treatment may be of the immersion type or the coating type. Examples of the immersion type chemical conversion treatment include chromate treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, and various chemical conversion treatments consisting of a mixture of these. On the other hand, examples of the coating type chemical conversion treatment include a method in which a coating agent having corrosion prevention properties is applied onto the barrier layer 13.
[0046] When forming at least a part of the corrosion prevention layer by any of these corrosion prevention treatments, namely, hydrothermal conversion treatment, anodizing treatment, and chemical conversion treatment, it is preferable to perform the above-mentioned degreasing treatment in advance. When using a degreased metal foil, such as a metal foil that has been subjected to an annealing process, as the barrier layer 13, there is no need to perform a degreasing treatment again in forming the corrosion prevention layers 14a and 14b.
[0047] The coating agent used in the spray-type chemical conversion treatment preferably contains trivalent chromium. The coating agent may also contain at least one polymer selected from the group consisting of cationic polymers and anionic polymers, which will be described later.
[0048] Among the above treatments, particularly in hydrothermal conversion treatment and anodization treatment, the aluminum foil surface is dissolved by a treatment agent to form an aluminum compound (boehmite, alumite) having excellent corrosion resistance. Therefore, since a bicontinuous structure is formed from the barrier layer 13 using the aluminum foil to the corrosion prevention treatment layers 14a, 14b, the above treatment is included in the definition of chemical conversion treatment. On the other hand, as described later, it is also possible to form the corrosion prevention treatment layers 14a, 14b by a pure coating method that is not included in the definition of chemical conversion treatment. As an example of this method, a method using a sol of a rare earth element oxide such as cerium oxide with an average particle size of 100 nm or less can be mentioned, which has an aluminum corrosion prevention effect (inhibitor effect) and is also environmentally friendly. By using this method, it is possible to impart a corrosion prevention effect to metal foils such as aluminum foils even with a general coating method.
[0049] Examples of the rare earth element oxide sol include sols using various solvents such as water-based, alcohol-based, hydrocarbon-based, ketone-based, ester-based, ether-based, etc. Among these, water-based sols are preferred.
[0050] In order to stabilize the dispersion of the rare earth oxide sol, inorganic acids such as nitric acid, hydrochloric acid, phosphoric acid, etc. or their salts, and organic acids such as acetic acid, malic acid, ascorbic acid, lactic acid, etc. are usually used as dispersion stabilizers. Among these dispersion stabilizers, phosphoric acid in particular is expected to (1) stabilize the dispersion of the sol, (2) improve adhesion to the barrier layer 13 by utilizing the aluminum chelating ability of phosphoric acid, and (3) improve the cohesive force of the corrosion prevention treatment layers 14a, 14b (oxide layers) by easily causing dehydration condensation of phosphoric acid even at low temperatures.
[0051] Examples of the phosphoric acid or salt thereof include orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid, or their alkali metal salts or ammonium salts. Among them, condensed phosphoric acids such as trimetaphosphoric acid, tetrametaphosphoric acid, hexametaphosphoric acid, and ultrametaphosphoric acid, or their alkali metal salts or ammonium salts are preferred for functional expression in the exterior material 10. In addition, in consideration of the drying film-forming properties (drying ability, amount of heat) when the corrosion prevention treatment layers 14a, 14b made of rare earth element oxide are formed by various coating methods using the sol of the rare earth element oxide, sodium salts are more preferred because of their excellent dehydration condensation properties at low temperatures. As for the phosphate, is preferably a water-soluble salt.
[0052] The compounding ratio of phosphoric acid (or a salt thereof) to the rare earth element oxide is preferably 1 to 100 parts by mass per 100 parts by mass of the rare earth element oxide. If the compounding ratio is 1 part by mass or more per 100 parts by mass of the rare earth element oxide, the rare earth element oxide sol becomes more stable, and the function of the exterior material 10 becomes better. The compounding ratio is more preferably 5 parts by mass or more per 100 parts by mass of the rare earth element oxide. Also, if the compounding ratio is 100 parts by mass or less per 100 parts by mass of the rare earth element oxide, the function of the rare earth element oxide sol is improved. The compounding ratio is more preferably 50 parts by mass or less, and even more preferably 20 parts by mass or less, per 100 parts by mass of the rare earth element oxide.
[0053] The corrosion prevention treatment layers 14a, 14b formed from the rare earth oxide sol are aggregates of inorganic particles, and therefore the cohesive strength of the layers themselves may be reduced even after the drying and curing process. Therefore, in this case, the corrosion prevention treatment layers 14a, 14b are preferably compounded with the following anionic polymer or cationic polymer to supplement the cohesive strength.
[0054] Examples of the anionic polymer include polymers having a carboxy group, such as poly(meth)acrylic acid (or a salt thereof) or a copolymer obtained by copolymerizing poly(meth)acrylic acid as a main component. Examples of the copolymerization components of this copolymer include alkyl(meth)acrylate monomers (alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, 2-ethylhexyl, cyclohexyl, etc.); (meth)acrylamide, N-alkyl(meth)acrylamide, N,N-dialkyl(meth)acrylamide (alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, 2-ethylhexyl, cyclohexyl, etc.), N-alkoxy(meth)acrylamide, N,N-dialkoxy(meth)acrylamide, (alkoxy)acrylamide, (meth ... Examples of the oxy group include a methoxy group, an ethoxy group, a butoxy group, and an isobutoxy group.) Amide group-containing monomers such as N-methylol (meth)acrylamide and N-phenyl (meth)acrylamide; hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; glycidyl group-containing monomers such as glycidyl (meth)acrylate and allyl glycidyl ether; silane-containing monomers such as (meth)acryloxypropyl trimethoxysilane and (meth)acryloxypropyl triethoxylane; and isocyanate group-containing monomers such as (meth)acryloxypropyl isocyanate.
[0055] These anionic polymers play a role in improving the stability of the corrosion prevention treatment layers 14a, 14b (oxide layers) obtained using the rare earth element oxide sol. This is achieved by the effect of protecting the hard and brittle oxide layer with the acrylic resin component, and the effect of capturing (cation catcher) ion contaminants (especially sodium ions) derived from phosphates contained in the rare earth element oxide sol. In other words, if the corrosion prevention treatment layers 14a, 14b obtained using the rare earth element oxide sol contain alkali metal ions such as sodium or alkaline earth metal ions, the corrosion prevention treatment layers 14a, 14b tend to deteriorate starting from the places containing these ions. Therefore, the resistance of the corrosion prevention treatment layers 14a, 14b is improved by fixing the sodium ions and the like contained in the rare earth element oxide sol using the anionic polymer.
[0056] The anti-corrosion treatment layers 14a, 14b, which are a combination of an anionic polymer and a rare earth oxide sol, have the same anti-corrosion performance as the anti-corrosion treatment layers 14a, 14b formed by chromate treatment of an aluminum foil. The anionic polymer is preferably a structure in which a polyanionic polymer, which is essentially water-soluble, is crosslinked. Examples of crosslinking agents used to form this structure include compounds having an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group.
[0057] Examples of compounds having an isocyanate group include diisocyanates such as tolylene diisocyanate, xylylene diisocyanate or hydrogenated products thereof, hexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate or hydrogenated products thereof, and isophorone diisocyanate; or polyisocyanates such as adducts obtained by reacting these isocyanates with polyhydric alcohols such as trimethylolpropane, biuret products obtained by reacting these isocyanates with water, or isocyanurate trimers; and blocked polyisocyanates obtained by blocking these polyisocyanates with alcohols, lactams, oximes, or the like.
[0058] Examples of compounds having a glycidyl group include epoxy compounds obtained by reacting glycols such as ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 14a,14b-butanediol, 1,6-hexanediol, and neopentyl glycol with epichlorohydrin; epoxy compounds obtained by reacting polyhydric alcohols such as glycerin, polyglycerin, trimethylolpropane, pentaerythritol, and sorbitol with epichlorohydrin; and epoxy compounds obtained by reacting dicarboxylic acids such as phthalic acid, terephthalic acid, oxalic acid, and adipic acid with epichlorohydrin.
[0059] Examples of compounds having a carboxy group include various aliphatic or aromatic dicarboxylic acids, etc. Also, poly(meth)acrylic acid and alkali (earth) metal salts of poly(meth)acrylic acid may be used.
[0060] Examples of compounds having an oxazoline group include low molecular weight compounds having two or more oxazoline units, and when a polymerizable monomer such as isopropenyloxazoline is used, copolymers of acrylic monomers such as (meth)acrylic acid, (meth)acrylic acid alkyl esters, and (meth)acrylic hydroxyalkyls can be mentioned.
[0061] Alternatively, the anionic polymer may be reacted with a silane coupling agent, more specifically, the carboxyl group of the anionic polymer may be selectively reacted with the functional group of the silane coupling agent, and the crosslinking point may be a siloxane bond. In this case, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-chloropropylmethoxysilane, vinyltrichlorosilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, etc. may be used. Among them, epoxysilane, aminosilane, and isocyanatesilane are preferable, especially considering the reactivity with the anionic polymer or its copolymer.
[0062] The ratio of these crosslinking agents to the anionic polymer is preferably 1 to 50 parts by mass, more preferably 10 to 20 parts by mass, per 100 parts by mass of the anionic polymer. If the ratio of the crosslinking agent is 1 part by mass or more per 100 parts by mass of the anionic polymer, the crosslinked structure is easily formed sufficiently. If the ratio of the crosslinking agent is 50 parts by mass or less per 100 parts by mass of the anionic polymer, the pot life of the coating liquid is improved.
[0063] The method for crosslinking the anionic polymer is not limited to the above-mentioned crosslinking agents, and may be a method for forming ionic crosslinks using titanium or zirconium compounds.
[0064] Examples of cationic polymers include polymers having amines, such as polyethyleneimine, ionic polymer complexes consisting of a polymer having polyethyleneimine and a carboxylic acid, primary amine-grafted acrylic resins in which a primary amine is grafted onto an acrylic main skeleton, polyallylamine or derivatives thereof, and cationic polymers such as aminophenol. Examples of polyallylamine include homopolymers or copolymers of allylamine, allylamine amide sulfate, diallylamine, and dimethylallylamine. These amines may be free amines or may be stabilized with acetic acid or hydrochloric acid. In addition, maleic acid, sulfur dioxide, and the like may be used as copolymer components. Furthermore, a type in which a primary amine is partially methoxylated to impart thermal crosslinking properties may be used, and aminophenol may also be used. In particular, allylamine or its derivatives are preferred.
[0065] The cationic polymer is preferably used in combination with a crosslinking agent having a functional group capable of reacting with amine / imine, such as a carboxy group or a glycidyl group. As the crosslinking agent to be used in combination with the cationic polymer, a polymer having a carboxylic acid that forms an ionic polymer complex with polyethyleneimine can also be used, and examples thereof include polycarboxylic acid (salt) such as polyacrylic acid or its ionic salt, or a copolymer having a comonomer introduced therein, and polysaccharides having a carboxy group such as carboxymethylcellulose or its ionic salt.
[0066] Cationic polymers are more preferred materials in terms of improving adhesion. In addition, cationic polymers are also water-soluble like the anionic polymers, so it is more preferred to form a crosslinked structure to impart water resistance. The crosslinking agent used to form a crosslinked structure in the cationic polymer can be the crosslinking agent described in the anionic polymer section. When a rare earth oxide sol is used as the corrosion prevention treatment layers 14a and 14b, a cationic polymer may be used as the protective layer instead of the anionic polymer.
[0067] The corrosion prevention treatment layer by chemical conversion treatment, such as chromate treatment, is formed on the aluminum foil by treating the aluminum foil with a chemical conversion treatment agent, particularly containing hydrofluoric acid, hydrochloric acid, nitric acid, sulfuric acid, or a salt thereof, and then forming a chemical conversion layer on the aluminum foil by applying a chromium or non-chromium compound. However, the above-mentioned chemical conversion treatment uses an acid as the chemical conversion treatment agent, which leads to deterioration of the working environment and corrosion of the coating device. On the other hand, unlike the chemical conversion treatment, such as chromate treatment, the above-mentioned coating type corrosion prevention treatment layers 14a and 14b do not need to form a gradient structure with respect to the barrier layer 13 using the aluminum foil. Therefore, the properties of the coating agent are not restricted by acidity, alkalinity, neutrality, etc., and a good working environment can be realized. In addition, the coating type corrosion prevention treatment layers 14a and 14b are preferable because alternatives to the chromate treatment using a chromium compound are required from the viewpoint of environmental hygiene.
[0068] From the above, examples of combinations of the above-mentioned coating-type corrosion prevention treatments include (1) only rare earth oxide sol, (2) only anionic polymer, (3) only cationic polymer, (4) rare earth oxide sol + anionic polymer (laminated composite), (5) rare earth oxide sol + cationic polymer (laminated composite), (6) (rare earth oxide sol + anionic polymer: laminated composite) / cationic polymer (multilayered), (7) (rare earth oxide sol + cationic polymer: laminated composite) / anionic polymer (multilayered), etc. Among them, (1) and (4) to (7) are preferred, and (4) to (7) are particularly preferred. However, this embodiment is not limited to the above combinations. For example, in the case of selecting a corrosion prevention treatment, a cationic polymer is a very preferable material because it has good adhesion to the modified polyolefin resin described below in the description of the adhesive resin layer. Therefore, in the case where the adhesive resin layer is composed of a modified polyolefin resin, it is possible to design the surface in contact with the adhesive resin layer to have a cationic polymer (for example, configurations such as (5) and (6)).
[0069] The corrosion prevention treatment layers 14a and 14b are not limited to the above-mentioned layers. For example, they may be formed using a treatment agent in which phosphoric acid and a chromium compound are mixed with a resin binder (such as aminophenol), as in the case of coating-type chromate, which is a known technology. By using this treatment agent, a layer having both corrosion prevention function and adhesion can be obtained. In addition, although it is necessary to consider the stability of the coating liquid, a coating agent in which a rare earth oxide sol and a polycationic polymer or a polyanionic polymer are mixed in advance into a one-component solution can be used to obtain a layer having both corrosion prevention function and adhesion.
[0070] The mass per unit area of the corrosion prevention layers 14a and 14b is 0.005 to 0.200 g / m2 regardless of whether the layer has a multi-layer structure or a single-layer structure. 2 is preferable, and 0.010 to 0.100 g / m 2 It is more preferable that the mass per unit area is 0.005 g / m 2 If the mass per unit area is 0.200 g / m or more, it is easy to impart a corrosion prevention function to the barrier layer 13. 2 Even if the thickness exceeds 100 mm, the corrosion prevention function does not change much. On the other hand, when a rare earth oxide sol is used, if the coating is thick, the heat curing during drying may be insufficient, which may result in a decrease in cohesive force. The thickness of the corrosion prevention layers 14a and 14b can be calculated from their specific gravity.
[0071] From the viewpoint of easily maintaining the adhesion between the sealant layer and the barrier layer, the corrosion prevention treatment layers 14a, 14b may be in an embodiment containing, for example, cerium oxide, 1 to 100 parts by mass of phosphoric acid or a phosphate relative to 100 parts by mass of the cerium oxide, and a cationic polymer, or may be formed by subjecting the barrier layer 13 to a chemical conversion treatment, or may be formed by subjecting the barrier layer 13 to a chemical conversion treatment and contain a cationic polymer.
[0072] <Second adhesive layer 12b> The second adhesive layer 12b is a layer that bonds the barrier layer 13 on which the second corrosion prevention treatment layer 14b is formed, and the sealant layer 16. For the second adhesive layer 12b, a general adhesive for bonding a barrier layer and a sealant layer can be used. Specific examples of materials constituting the second adhesive layer 12b include polyurethane resins in which a bifunctional or higher isocyanate compound is reacted with a base material such as polyester polyol, polyether polyol, acrylic polyol, or carbonate polyol.
[0073] The various polyols described above can be used alone or in combination of two or more kinds depending on the functions and performance required for the exterior material.
[0074] Depending on the performance required for the adhesive, various other additives and stabilizers may be blended with the polyurethane resin described above.
[0075] In the packaging material 10 of the present embodiment, the second adhesive layer 12b may be the specific adhesive layer described above.
[0076] The thickness of the second adhesive layer 12b is not particularly limited, but from the viewpoint of obtaining the desired adhesive strength, processability, and the like, it is preferably 1 to 10 μm, and more preferably 3 to 7 μm.
[0077] When the second adhesive layer 12b is a specific adhesive layer, the mass per unit area of the adhesive layer 12b is set to 2.0 to 6.0 g / m2 from the viewpoint of ensuring superior lamination strength both in room temperature and high temperature environments and obtaining superior deep drawability. 2 and 2.5 to 5.0 g / m 2 and 3.5 to 4.5 g / m 2 may be also possible.
[0078] <Sealant layer 16> The sealant layer 16 is a layer that provides heat sealing to the exterior material 10. Examples of the sealant layer 16 include resin films made of polyolefin resins or polyester resins. The resins constituting the sealant layer 16 (hereinafter also referred to as "base resins") may be used alone or in combination of two or more.
[0079] Examples of polyolefin resins include low-, medium- or high-density polyethylene; ethylene-α-olefin copolymers; polypropylene; block or random copolymers containing propylene as a copolymerization component; and propylene-α-olefin copolymers.
[0080] Examples of polyester resins include polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polyethylene naphthalate (PEN) resin, polybutylene naphthalate (PBN) resin, and polytrimethylene terephthalate (PTT) resin.
[0081] The sealant layer 16 may contain a polyolefin-based elastomer. The polyolefin-based elastomer may be compatible with the above-mentioned base resin or may not be compatible with it, and may contain both a compatible polyolefin-based elastomer that is compatible and a non-compatible polyolefin-based elastomer that is not compatible with it. Being compatible (compatible system) means that the elastomer disperses in the base resin with a dispersed phase size of 1 nm or more and less than 500 nm. Not being compatible (non-compatible system) means that the elastomer disperses in the base resin with a dispersed phase size of 500 nm or more and less than 20 μm.
[0082] When the base resin is a polypropylene resin, the compatible polyolefin elastomer may be, for example, a propylene-butene-1 random copolymer, and the incompatible polyolefin elastomer may be, for example, an ethylene-butene-1 random copolymer. The polyolefin elastomers may be used alone or in combination of two or more.
[0083] Furthermore, the sealant layer 16 may contain, as additive components, for example, slip agents, antiblocking agents, antioxidants, light stabilizers, flame retardants, etc. The content of these additive components is preferably 5 parts by mass or less, assuming that the total mass of the sealant layer 16 is 100 parts by mass.
[0084] The thickness of the sealant layer 16 is not particularly limited, but from the viewpoint of achieving both a thin film and improved heat seal strength in a high-temperature environment, it is preferably in the range of 5 to 100 μm, more preferably in the range of 10 to 100 μm, and even more preferably in the range of 20 to 80 μm.
[0085] The sealant layer 16 may be either a single-layer film or a multi-layer film, and may be selected depending on the required function.
[0086] Although a preferred embodiment of the exterior material for a power storage device according to the present embodiment has been described in detail above, the present disclosure is not limited to such a specific embodiment, and various modifications and variations are possible within the scope of the gist of the present disclosure as described in the claims.
[0087] For example, FIG. 1 shows a case where the corrosion prevention layers 14a and 14b are provided on both sides of the barrier layer 13, but only one of the corrosion prevention layers 14a and 14b may be provided. Alternatively, a corrosion prevention treatment layer may be provided, or a corrosion prevention treatment layer may not be provided.
[0088] While Fig. 1 shows a case where the barrier layer 13 and the sealant layer 16 are laminated using the second adhesive layer 12b, the barrier layer 13 and the sealant layer 16 may be laminated using an adhesive resin layer 15 as in the exterior packaging material 20 for an electricity storage device shown in Fig. 2. In addition, in the exterior packaging material 20 for an electricity storage device shown in Fig. 2, the second adhesive layer 12b may be provided between the barrier layer 13 and the adhesive resin layer 15.
[0089] <Adhesive resin layer 15> The adhesive resin layer 15 is generally composed of an adhesive resin composition as a main component and additive components as necessary. The adhesive resin composition is not particularly limited, but preferably contains a modified polyolefin resin.
[0090] The modified polyolefin resin is preferably a polyolefin resin graft-modified with an unsaturated carboxylic acid derivative derived from an unsaturated carboxylic acid, an acid anhydride, or an ester thereof.
[0091] Examples of polyolefin resins include low density polyethylene, medium density polyethylene, high density polyethylene, ethylene-α-olefin copolymer, homopolypropylene, block polypropylene, random polypropylene, and propylene-α-olefin copolymer.
[0092] The modified polyolefin resin is preferably a polyolefin resin modified with maleic anhydride. For example, "Admer" manufactured by Mitsui Chemicals, Inc. and "Modic" manufactured by Mitsubishi Chemical Corporation are suitable for the modified polyolefin resin. Since such modified polyolefin resins have excellent reactivity with various metals and polymers having various functional groups, the adhesive resin layer 15 can be given adhesion by utilizing the reactivity, and the electrolyte resistance can be improved. In addition, the adhesive resin layer 15 may contain various additives such as various compatible and incompatible elastomers, flame retardants, slip agents, antiblocking agents, antioxidants, light stabilizers, and tackifiers, as necessary.
[0093] The thickness of the adhesive resin layer 15 is not particularly limited, but from the viewpoints of stress relaxation and moisture / electrolyte permeability, it is preferably the same as or less than that of the sealant layer 16 .
[0094] In addition, in the exterior packaging material 20 for a storage battery device, the total thickness of the adhesive resin layer 15 and the sealant layer 16 is preferably in the range of 5 to 100 μm, and more preferably in the range of 20 to 80 μm, from the viewpoint of achieving both a thin film and improved heat seal strength in a high-temperature environment.
[0095] [Exterior material manufacturing method] Next, there will be described an example of a method for manufacturing the exterior packaging material 10 shown in Fig. 1. Note that the method for manufacturing the exterior packaging material 10 is not limited to the following method.
[0096] The manufacturing method of the exterior material 10 of this embodiment is roughly composed of a step of providing corrosion prevention treatment layers 14a, 14b on the barrier layer 13, a step of bonding the base material layer 11 and the barrier layer 13 together using a first adhesive layer 12a, a step of further laminating a sealant layer 16 via a second adhesive layer 12b to produce a laminate, and a step of, if necessary, subjecting the obtained laminate to an aging treatment.
[0097] (Laminating process of corrosion prevention treatment layers 14a, 14b on barrier layer 13) This step is a step of forming the corrosion prevention treatment layers 14a, 14b on the barrier layer 13. As described above, examples of the method include subjecting the barrier layer 13 to a degreasing treatment, a hydrothermal conversion treatment, an anodizing treatment, or a chemical conversion treatment, or applying a coating agent having corrosion prevention properties.
[0098] Furthermore, when the corrosion prevention treatment layers 14a, 14b are multiple layers, for example, a coating liquid (coating agent) constituting the lower corrosion prevention treatment layer (barrier layer 13 side) may be applied to the barrier layer 13 and baked to form a first layer, and then a coating liquid (coating agent) constituting the upper corrosion prevention treatment layer may be applied to the first layer and baked to form a second layer.
[0099] The degreasing treatment may be performed by spraying or immersion. The hydrothermal conversion treatment and anodizing treatment may be performed by immersion. The chemical conversion treatment may be performed by an appropriate method such as immersion, spraying, or coating, depending on the type of chemical conversion treatment.
[0100] Regarding the coating method of the coating agent having corrosion prevention properties, various methods such as gravure coating, reverse coating, roll coating, bar coating, etc. can be used.
[0101] As described above, the various treatments may be performed on either one or both sides of the metal foil, but in the case of one-sided treatment, the treated side is preferably the side on which the sealant layer 16 is laminated. If required, the surface of the base layer 11 may also be subjected to the above treatments.
[0102] The amount of coating agent applied to form the first layer and the second layer is 0.005 to 0.200 g / m 2 is preferable, and 0.010 to 0.100 g / m 2 is more preferred.
[0103] Furthermore, when dry curing is required, it can be performed at a base material temperature in the range of 60 to 300° C. depending on the drying conditions of the corrosion prevention treatment layers 14a and 14b used.
[0104] (Step of bonding the base layer 11 and the barrier layer 13) This step is a step of bonding the barrier layer 13 provided with the corrosion prevention treatment layers 14a, 14b to the base material layer 11 via the first adhesive layer 12a. The bonding method may be dry lamination, non-solvent lamination, wet lamination, or the like, and the two are bonded together using the material constituting the first adhesive layer 12a described above. The first adhesive layer 12a has a dry coating amount of 1 to 10 g / m. 2 More preferably, it is in the range of 2 to 6 g / m 2 It is set within the range.
[0105] (Laminating step of second adhesive layer 12b and sealant layer 16) This step is a step of bonding the sealant layer 16 via the second adhesive layer 12b to the second corrosion prevention treatment layer 14b side of the barrier layer 13. Examples of the bonding method include a wet process and dry lamination.
[0106] In the case of the wet process, the solution or dispersion of the adhesive constituting the second adhesive layer 12b is applied onto the second corrosion prevention treatment layer 14b, and the solvent is removed at a predetermined temperature to form a dry film, or the dry film is baked as necessary after the dry film is formed. Then, the sealant layer 16 is laminated to produce the exterior material 10. Examples of the coating method include the various coating methods exemplified above. The preferred dry coating amount of the second adhesive layer 12b is the same as that of the first adhesive layer 12a.
[0107] In this case, the sealant layer 16 can be produced, for example, by a melt extrusion molding machine using a resin composition for forming a sealant layer containing the above-mentioned components of the sealant layer 16. From the viewpoint of productivity, the melt extrusion molding machine can be processed at a processing speed of 80 m / min or more. Cut.
[0108] (Aging process) This step is a step of aging (curing) the laminate. By aging the laminate, it is possible to promote adhesion between the barrier layer 13, the second corrosion prevention treatment layer 14b, the second adhesive layer 12b, and the sealant layer 16. The aging treatment can be carried out at a temperature in the range of room temperature to 100°C. The aging time is, for example, 1 to 10 days.
[0109] In this manner, the exterior packaging material 10 of the present embodiment as shown in FIG. 1 can be manufactured.
[0110] Next, a description will be given of an example of a method for manufacturing the exterior material 20 shown in Fig. 2. Note that the method for manufacturing the exterior material 20 is not limited to the following method.
[0111] The manufacturing method of the exterior material 20 of this embodiment is generally configured to include a step of providing the corrosion prevention treatment layers 14a, 14b on the barrier layer 13, a step of bonding the base material layer 11 and the barrier layer 13 together using the first adhesive layer 12a, a step of further laminating the adhesive resin layer 15 and the sealant layer 16 to prepare a laminate, and a step of heat treating the obtained laminate, if necessary. Note that the steps up to the step of bonding the base material layer 11 and the barrier layer 13 can be performed in the same manner as the manufacturing method of the exterior material 10 described above.
[0112] (Laminating Step of Adhesive Resin Layer 15 and Sealant Layer 16) This step is a step of forming an adhesive resin layer 15 and a sealant layer 16 on the second corrosion prevention treatment layer 14b formed in the previous step. The method includes a method of sand laminating the adhesive resin layer 15 together with the sealant layer 16 using an extrusion laminator. Furthermore, lamination is also possible by a tandem lamination method in which the adhesive resin layer 15 and the sealant layer 16 are extruded, or a co-extrusion method. In forming the adhesive resin layer 15 and the sealant layer 16, for example, each component is blended so as to satisfy the above-mentioned configuration of the adhesive resin layer 15 and the sealant layer 16. The above-mentioned resin composition for forming the sealant layer is used to form the sealant layer 16.
[0113] This process produces a laminate in which the layers are stacked in the following order: base layer 11 / first adhesive layer 12a / first corrosion prevention treatment layer 14a / barrier layer 13 / second corrosion prevention treatment layer 14b / adhesive resin layer 15 / sealant layer 16, as shown in FIG. 2.
[0114] The adhesive resin layer 15 may be laminated by directly extruding the materials dry-blended to have the above-mentioned material composition using an extrusion laminator. Alternatively, the adhesive resin layer 15 may be laminated by extruding the granulated material, which has been melt-blended in advance using a melt kneading device such as a single-screw extruder, a twin-screw extruder, or a Brabender mixer, using an extrusion laminator.
[0115] The sealant layer 16 may be laminated by directly extruding, by an extrusion laminator, materials dry-blended to have the above-mentioned material composition as the constituents of the resin composition for forming a sealant layer. Alternatively, the adhesive resin layer 15 and the sealant layer 16 may be laminated by a tandem lamination method in which the adhesive resin layer 15 and the sealant layer 16 are extruded by an extrusion laminator using a granulated product obtained by melt blending in advance using a melt kneading device such as a single screw extruder, a twin screw extruder, or a Brabender mixer, or by a co-extrusion method. Alternatively, a sealant monolayer may be formed in advance as a cast film using the resin composition for forming a sealant layer, and this film may be laminated together with an adhesive resin by sand lamination. The formation speed (processing speed) of the adhesive resin layer 15 and the sealant layer 16 may be determined from the viewpoint of productivity. For example, it can be 80 m / min or more.
[0116] (Heat treatment process) This step is a step of heat-treating the laminate. Heat-treating the laminate can improve adhesion between the barrier layer 13, the second corrosion prevention treatment layer 14b, the adhesive resin layer 15, and the sealant layer 16. As a method of heat treatment, it is preferable to treat at a temperature at least equal to or higher than the melting point of the adhesive resin layer 15.
[0117] In this manner, the exterior material 20 of this embodiment as shown in FIG. 2 can be manufactured.
[0118] Although preferred embodiments of the exterior material for a power storage device according to the present disclosure have been described in detail above, the present disclosure is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the gist of the present disclosure as described in the claims.
[0119] The exterior material for an electricity storage device according to the present disclosure can be suitably used as an exterior material for an electricity storage device such as, for example, a secondary battery such as a lithium ion battery, a nickel-metal hydride battery, and a lead-acid battery, and an electrochemical capacitor such as an electric double layer capacitor, etc. In particular, the exterior material for an electricity storage device according to the present disclosure is suitable as an exterior material for an all-solid-state battery using a solid electrolyte.
[0120] [Electricity storage device] FIG. 3 is a perspective view showing one embodiment of a power storage device produced using the above-mentioned exterior material. As shown in FIG. 3, the power storage device 50 includes a battery element (power storage device main body) 52, two metal terminals (current extraction terminals) 53 for extracting current from the battery element 52 to the outside, and an exterior material 10 that hermetically encloses the battery element 52. The exterior material 10 is the exterior material 10 according to the present embodiment described above. In the exterior material 10, the base material layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. That is, the exterior material 10 is folded in two so that the base material 11 is on the outer side of the power storage device 50 and the sealant layer 16 is on the inner side of the power storage device 50, one of which is deep-draw molded, and then heat-sealed to accommodate and seal the battery element 52 inside. Alternatively, one of the two exterior materials 10 may be deep-draw molded, and then the other exterior material 10 may be placed on top of it and heat-sealed to form a power storage device 50 that contains and seals the battery element 52 therein. Note that in the power storage device 50, an exterior material 20 may be used instead of the exterior material 10.
[0121] Battery element 52 is formed by interposing an electrolyte between a positive electrode and a negative electrode. Metal terminal 53 is a part of a current collector taken out from exterior material 10, and is made of a metal foil such as copper foil or aluminum foil.
[0122] The electricity storage device 50 of this embodiment may be an all-solid-state battery. In this case, a solid electrolyte such as a sulfide-based solid electrolyte is used as the electrolyte of the battery element 52. Since the electricity storage device 50 of this embodiment uses the exterior material 10 of this embodiment, excellent laminate strength can be ensured even when used in a high-temperature environment. EXAMPLES
[0123] The present disclosure will be described more specifically below based on examples, but the present disclosure is not limited to the following examples.
[0124] [Materials used] The materials used in the examples and comparative examples are shown below.
[0125] As the base material layer 11, a nylon (Ny) film (manufactured by Toyobo Co., Ltd.) having a thickness of 25 μm and having one surface subjected to a corona treatment was used.
[0126] Next, five types of polyamideimides having different number average molecular weights (Mn) were prepared as materials for forming the first adhesive layer 12a.
[0127] The number average molecular weights (Mn) of the polyamideimides are 2,000, 5,000, 20,000, 30,000 and 40,000, respectively.
[0128] In addition, polyether polyol, polyester polyol, acrylic polyol, and polycarbonate polyol (PCD) were prepared as the base material (polyol resin) of the polyurethane compound constituting the first adhesive layer 12a. In addition, an adduct of hexamethylene diisocyanate (HDI-a), a nurate of isophorone diisocyanate (IPDI-n), and an adduct of tolylene diisocyanate (TDI-a) were prepared as the curing agent (polyfunctional isocyanate compound) of the polyurethane compound.
[0129] A soft aluminum foil (manufactured by Toyo Aluminum, "8079 material") with corrosion prevention treatment layers 14a and 14b on both sides was used as the barrier layer 13. The corrosion prevention treatment layers 14a and 14b were formed using sodium polyphosphate-stabilized cerium oxide sol produced by mixing 100 parts by mass of cerium oxide with 10 parts by mass of sodium salt of phosphoric acid.
[0130] Next, as the adhesive constituting the second adhesive layer 12b, a polyurethane adhesive was used, which was made by blending polyisocyanate with acid-modified polyolefin dissolved in a mixed solvent of toluene and methylcyclohexane. The second adhesive layer 12b had a thickness of 3 g / m 2 It was formed by coating.
[0131] A polyolefin film (a non-oriented polypropylene film whose surface facing the second adhesive layer was corona-treated) was used as the sealant layer 16. The thickness of the sealant layer 16 was 80 μm.
[0132] [Preparation of exterior material 10] Example 1 The exterior material 10 of this example was prepared as follows. Table 1 shows the number average molecular weight (Mn) and blending amount A (solid content of polyamideimide resin relative to solid content of polyurethane compound) of the polyamideimide used, as well as the ratio of the number of isocyanates contained therein to the base agent and curing agent of the polyurethane compound (NCO / OH).
[0133] That is, the barrier layer 13 was attached to the base material layer 11 by a dry lamination technique using a first adhesive (first adhesive layer) 12a. The lamination of the barrier layer 13 and the base material layer 11 was performed by applying the first adhesive onto one surface of the barrier layer 13, drying it at 80°C for 1 minute, laminating it with the base material layer 11, and aging it at 80°C for 120 hours.
[0134] Next, the surface of the barrier layer 13 opposite to the base layer 11 side was attached to a sealant layer (thickness 80 μm) 16 using a polyurethane adhesive (second adhesive layer) 12b by a dry lamination technique. The lamination of the barrier layer 13 and the sealant layer 16 was performed by applying a polyurethane adhesive to the surface of the barrier layer 13 opposite to the base layer 11 side, drying at 80° C. for 1 minute, laminating with the sealant layer, and aging at 120° C. for 3 hours. In this manner, an exterior material (laminate of base layer 11 / first adhesive layer 12a / barrier layer 13 / second adhesive layer 12b / sealant layer 16) 10 was produced.
[0135] (Comparative Examples 1 to 4) These Comparative Examples 1 to 4 were prepared by comparing the effect of the presence or absence of polyamideimide with that of Example 1, which contained polyamideimide. The number average molecular weight (Mn) and the amount A of the polyamideimide used in each Comparative Example, as well as the base agent, curing agent, and NCO / OH of the polyurethane compound are shown in Table 1.
[0136] (Examples 2 to 5) These examples are intended to investigate the influence of the blend amount A of polyamideimide by comparing with Example 1. Table 1 shows the number average molecular weight (Mn) and blend amount A of polyamideimide, as well as the base agent, curing agent, and NCO / OH of the polyurethane compound.
[0137] (Examples 6 to 9) These examples are intended to investigate the effect of the number average molecular weight (Mn) of polyamideimide by comparing with Example 1. Table 1 shows the number average molecular weight (Mn) and blend amount A of polyamideimide, as well as the base agent, curing agent, and NCO / OH of the polyurethane compound.
[0138] (Examples 10 to 12) These examples are intended to investigate the influence of the type of base agent of the polyurethane-based compound by comparing with Example 1. Table 1 shows the number average molecular weight (Mn) and blend amount A of polyamideimide, and the base agent, curing agent, and NCO / OH of the polyurethane-based compound.
[0139] (Examples 13 to 14) These examples are intended to investigate the influence of the type of curing agent for polyurethane compounds by comparing with Example 1. Table 1 shows the number average molecular weight (Mn) and blend amount A of polyamideimide, as well as the base agent, curing agent, and NCO / OH of the polyurethane compounds.
[0140] (Examples 15 to 19) These examples are intended to investigate the influence of NCO / OH of polyurethane compounds by comparing with Example 1. Table 1 shows the number average molecular weight (Mn) and blend amount A of polyamideimide, and the base agent, curing agent, and NCO / OH of the polyurethane compounds.
[0141] [Exterior material 10 evaluation] The exterior packaging materials 10 produced in each of the examples and comparative examples were evaluated from four viewpoints: evaluation by measuring the laminate strength in a room temperature environment, evaluation by measuring the laminate strength in a high temperature (170°C) environment, evaluation of deep draw formability, and evaluation of the reliability (molding reliability) of the exterior packaging material 10 after molding in a high temperature (170°C) environment.
[0142] (Measurement of laminate strength at room temperature) The laminate strength between the barrier layer and the base layer of the exterior material cut to a width of 15 mm was measured at room temperature (25°C) using a 90-degree peel test with a tensile tester (manufactured by Shimadzu Corporation) at a tensile speed of 50 mm / min. The laminate strength was evaluated according to the following criteria. The results are shown in Table 1. A: Lamination strength is 6.0N / 15mm or more. B: Lamination strength is 4.5N / 15mm or more and less than 6.0N / 15mm. C: Lamination strength is 3.0N / 15mm or more and less than 4.5N / 15mm. D: Lamination strength is less than 3.0N / 15mm.
[0143] (Measurement of laminate strength in high temperature environment) The exterior material cut to a width of 15 mm was left in a high-temperature environment at 170°C for 5 minutes. After that, the laminate strength between the barrier layer and the base material layer of the exterior material in a 150°C environment was measured at a tensile speed of 50 mm. The lamination strength was measured by a 90-degree peel test using a tensile tester (manufactured by Shimadzu Corporation) at a rate of 100000000 / min. The laminate strength was evaluated according to the following criteria. The results are shown in Table 1. A: Lamination strength is 3.0N / 15mm or more. B: Lamination strength is 2.0N / 15mm or more and less than 3.0N / 15mm. C: Laminate strength is 1.0N / 15mm or more and less than 2.0N / 15mm. D: Lamination strength is less than 1.0N / 15mm.
[0144] (Evaluation of deep drawing formability) The molding depth at which deep drawing was possible for exterior materials was evaluated by the following method. The molding depth of the molding device was set to 1.00 to 5.00 mm in increments of 0.25 mm, and the exterior materials were deep-draw molded. The samples after deep drawing were visually checked for the presence or absence of breaks and pinholes while shining a light on the samples, and the maximum molding depth at which deep drawing was possible without the occurrence of either breaks or pinholes was determined. The molding depth was also evaluated according to the following criteria. The results are shown in Table 1. A: The maximum molding depth is 4.00 mm or more. B: The maximum molding depth is 3.50 mm or more and less than 4.00 mm. C: The maximum molding depth is 3.00 mm or more and less than 3.50 mm. D: The maximum molding depth is less than 3.00 mm.
[0145] (Evaluation of molding reliability) The samples (five specimens each) with a mold depth of 2.00 mm prepared for the above deep drawability evaluation were stored in an environment at 170°C for one week. After that, the samples were visually inspected while shining a light on the vicinity of the molded convex parts, and the occurrence of delamination between the base layer and the barrier layer was examined, and the molding reliability was evaluated according to the following criteria. The results are shown in Table 1. A: The incidence of delamination was 0 out of 5 samples. B: The occurrence of delamination was 1 to 2 out of 5 specimens. C: The occurrence of delamination was 3 or more out of 5 samples.
[0146] [Table 1]
[0147] [Investigation] (Investigation on the Influence of the Presence or Absence of Polyamide Imide Blending) From the results of Example 1 and Comparative Examples 1 to 4, although there is no significant difference in the laminate strength at room temperature environment depending on the presence or absence of polyamide imide blending, the performance of the laminate strength and the deep drawing formability at high temperature environment is greatly improved by the blending of polyamide imide. Also, the same applies to the reliability (molding reliability) of the exterior material 10 at high temperature environment after molding.
[0148] Note that although the polyurethane-based compound composed of the reaction product of polyester polyol and IPDI-n is said to have relatively high heat resistance, Example 1 blended with polyamide imide is also excellent in terms of laminate strength and molding reliability at high temperature environment compared with Comparative Examples 3 and 4 using this. Moreover, although NCO / OH is increased in Comparative Example 4 to further improve the heat resistance, Example 1 is superior to this.
[0149] (Investigation on the Blending Amount A of Polyamide Imide) From the results of Examples 1 to 4, it can be understood that the higher the blending amount A of polyamide imide (the solid content of polyamide imide resin with respect to the solid content of the polyurethane-based compound), the more the laminate strength and molding reliability at high temperature environment are improved. However, in Example 5 where this blending amount A reached 20.0 mass%, the laminate strength at high temperature environment was lower than that of Examples 1 to 4 with a blending amount A of 15.0 mass% or less, and moreover, the deep drawing formability was greatly reduced.
[0150] Therefore, in order to achieve both the laminate strength and molding reliability at high temperature environment, it can be seen that the blending amount A of polyamide imide may be 1.0 mass% < A < 20.0 mass%. The one with the most excellent laminate strength at high temperature environment is 10.0 to 15.0 mass%.
[0151] (Investigation on the Number Average Molecular Weight (Mn) of Polyamide Imide) From the results of Examples 1, 6 to 9, it can be understood that when the number average molecular weight (Mn) of the polyamideimide resin satisfies 3000 < Mn < 36000 (Examples 6 to 8), the laminate strength under high temperature environment is excellent, and within this range, it can be understood that the smaller the number average molecular weight (Mn), the better. Although the reason is not clear, for example, it can be speculated that in the case of a low molecular weight polyamideimide resin, the number of functional groups per unit mass is large, which is related to excellent interfacial adhesion.
[0152] In addition, when the number average molecular weight (Mn) is less than 5000 (Example 1), the laminate strength under high temperature environment is lower compared to the case where it is larger (Examples 6 to 9). Thus, when the number average molecular weight (Mn) is less than 5000, it can be speculated that as the number of functional groups per unit mass increases, the brittleness of the polyamideimide increases, and it is related to the decrease in the melting point, glass transition temperature, softening point, etc., resulting in a decrease in its heat resistance.
[0153] In addition, when the number average molecular weight (Mn) of the polyamideimide becomes larger than 36000 (Example 9), such a high molecular weight polyamideimide does not dissolve in the solvent, and therefore, the composition containing it cannot be used as an adhesive.
[0154] (Consideration on the type of main component of the polyurethane-based compound) From the results of Examples 1, 10 to 12, when using a polyester polyol, an acrylic polyol, or a polycarbonate polyol (PCD) as the main component (polyol resin) of the polyurethane-based compound (Examples 10 to 12), it can be understood that the laminate strength under high temperature environment is better than when using a polyether polyol (Example 1). Among these, when using a polyester polyol (Example 10), the laminate strength under high temperature environment is better than when using an acrylic polyol or PCD (Examples 11, 12). In addition, it is also excellent in deep drawing moldability and molding reliability.
[0155] (Consideration on the type of curing agent for polyurethane-based compounds) From the results of Examples 1, 13, and 14, it can be understood that when using alicyclic IPDI-n or TDI-a containing an aromatic ring in the molecular structure as the curing agent (polyfunctional isocyanate compound) of the polyurethane-based compound (Example 13, 14), the laminate strength in a high-temperature environment is superior to the case of using aliphatic HDI-a (Example 1). Also, it is excellent in deep drawing formability and molding reliability.
[0156] (Consideration on NCO / OH of polyurethane-based compounds) From the results of Examples 1, 15 to 19, it can be understood that if the NCO / OH of the polyurethane-based compound satisfies 1.5 < NCO / OH < 40.0 (Examples 1, 15 to 19), the laminate strength, deep drawing formability, and molding reliability can all be improved in a high-temperature environment. In particular, when NCO / OH is 10.0 to 30.0 (Examples 16 to 18), it is excellent in both laminate strength and deep drawing formability in a high-temperature environment.
Explanation of symbols
[0157] 10…Outer packaging material for power storage device 11…Base material 12a…First adhesive layer 12b…Second adhesive layer 13…Barrier layer 14a…First corrosion prevention treatment layer 14b…Second corrosion prevention treatment layer 15…Adhesive resin layer 16…Sealant layer 20…Outer packaging material for power storage device 50…Power storage device, 52…Battery element, 53…Metal terminal
Claims
1. An exterior material for an electricity storage device comprising at least a base layer, a barrier layer, and a sealant layer in this order, an adhesive layer including a polyurethane compound and a polyamideimide resin is provided between the base layer and the barrier layer; In the adhesive layer, the solid content (A) of the polyamide-imide resin relative to the solid content of the polyurethane compound is 1.0 mass% < A < 20.0 mass%, The number average molecular weight (Mn) of the polyamide-imide resin is 3000<Mn<36000, the polyurethane-based compound is a reaction product of at least one polyol resin and at least one polyfunctional isocyanate compound; the polyol resin is at least one polyol resin selected from the group consisting of polyester polyols, acrylic polyols, and polycarbonate polyols; the polyfunctional isocyanate compound is at least one kind of isocyanate polymer selected from the group consisting of alicyclic isocyanate polymers and isocyanate polymers containing an aromatic ring in the molecular structure; an outer casing material for a power storage device, wherein a ratio (NCO / OH) of the number of isocyanate groups contained in the polyfunctional isocyanate compound to the number of hydroxyl groups contained in the polyol resin is 1.5<NCO / OH<40.
0.
2. The exterior material for a power storage device according to claim 1 , which is for an all-solid-state battery.
3. A power storage device main body; a current extracting terminal extending from the power storage device body; The exterior material for an electric storage device according to claim 1 or 2, which holds the current extracting terminal and houses the electric storage device main body; A power storage device comprising:
Citation Information
Patent Citations
External facing material for power storage device
JP2013101765A
Exterior package material for power storage device, and power storage device
JP2019117706A
Adhesive for laminating metal foil and resin film, laminated body, packaging material for battery exterior, and battery case and method for manufacturing same
WO2016199551A1
Battery packaging material adhesive, battery packaging material, battery container, and battery
WO2018117080A1